Nutritional approaches for gastroparesis. (November 2020) - Limketkai, Berkeley N; LeBrett, Wendi; Lin, Lisa; Shah, Neha D
Summary: Patients with gastroparesis often have signs and symptoms including nausea, vomiting, epigastric discomfort, and early satiety, thus leading to inadequate food intake and a high risk of malnutrition. There is a considerable scarcity of data about nutritional strategies for gastroparesis, and current practices rely on extrapolated evidence. Some approaches include the modification of food composition, food consistency, and food volume in the context of delayed gastric emptying. If the patient is unable to consume adequate calories through a solid food diet, stepwise nutritional interventions could include the use of liquid meals, oral nutrition supplements, enteral nutrition, and parenteral nutrition. This Review discusses the role, rationale, and current evidence of diverse nutritional interventions in the management of gastroparesis.